(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the taxonomic frameworks used to describe composite sentences, focusing on classifications such as collotaxeme, parataxeme, hypertaxeme (and its variations), binome, polynome, discourseme, cumulene, and occursome. These categories provide a systematic approach to analyzing the structural and functional relationships between clauses. The study presents new insights into how composite sentences convey complex ideas in discourse, highlighting their essential role in syntactic analysis and linguistic research.